"Keep Pressing On": Spiritual Epistemology and Its Role in the Collegiate Lives of Black Gay and Bisexual Men. Issue 1 (2nd January 2016) - Means, Darris R.; Jaeger, Audrey J.
Abstract: This qualitative study explores how the spiritual epistemology of Black, gay and bisexual, cisgender men in college changed during their spiritual journeys and how participants used spirituality in their collegiate lives. External forces, such as family members, religious text, and church settings, initially shaped many participants' spirituality, but their spirituality expanded to integrate participants' passions and interests, such as science and music, as they moved towards developing their own spiritual guidelines. Students also used their spirituality as a source of motivation during college and a guide for collegiate decisions.